Predictors of dating violence in college girls and differences from non-dating violence in psychiatric outcomes - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: In this study, it was aimed to examine variables that predict exposure to dating violence, students' views about violence and to determine differences with non-dating violence in terms of mental problems. Methods: Eight hundred and forty-eight college girls were included in the study by random sampling. A questionnaire assessing sociodemographic and violence related variables, and scales assessing depression, anxiety, thought of suicide, and suicidal behavior were filled by students. Psychiatric diagnostic interview was conducted with students who had been physically abused during the past 12 months. Results: The frequency of dating physical violence for the whole group was 3.7% (n=31) and the frequency of psychological violence by flirting was 24.8% (n=210). As a result of the logistic regression analysis, it was shown that staying in dormitories had a predictive effect on dating violence. Significant differences were found in depression, anxiety and suicide scores between students who were exposed to dating and non-dating violence. There was no significant difference in the rates of psychiatric disorder among girls who were exposed to physical violence by dating and non-dating in the last 12 months. Discussion: Our study is the first study in the related literature to compare rates of psychiatric disorders, to assess the level of depression, anxiety and suicidality in college girls who were exposed to dating and/or non-dating violence. The predictive effect of staying in dormitories on dating violence is a remarkable finding and can be examined with multicentre, large sample studies. Physical violence negatively affects mental health regardless of the perpetrator's closeness. Development of programs to prevent physical abuse is important.
Keywords: dating violence; non-dating violence; psychiatric disorders; college girls; INTIMATE PARTNER VIOLENCE; STUDENTS; HEALTH; RISK